Roles of humic acid on vivianite crystallization in heterogeneous nucleation for phosphorus recovery. (20th September 2022) - Li, Qi; Liu, Xiaocheng; Hou, Nannan; Wang, Jing; Wang, Yi-Ran; Li, Wen-Qiang; Chen, Jia-Qi; Mu, Yang
Abstract: Vivianite crystallization serves as an intriguing alternative for phosphorus recovery from wastewater, while the impact of humic acid on this technology especially in heterogeneous nucleation is still lacking. This study found that the presence of humic acid in a range of 0–50 mg/L increased the size of crystals from 4.92 ± 0.06 to 8.48 ± 0.16 μm during vivianite crystallization in heterogeneous nucleation. Both experiments and density functional theory calculations revealed that carboxyl groups, the key functional group in humic acid, could initially reduce heterogeneous nucleation rate by elongate the average bond of Fe–O(-P), then increasing the growth rate of vivianite crystallization through reducing the surface charge of crystals, and thus leading to the increase in vivianite size. Compared with aromatic one, this study further elucidated that aliphatic carboxyl groups in humic acid with stronger binding ability and less steric hindrance could lead to lower heterogeneous nucleation and higher growth rates, resulting in larger vivianite crystals. This study may provide us a better understanding on vivianite crystallization for phosphorus recovery from wastewater. Graphical abstract: Image 1 Highlights: Humic acid increased the size of vivianite crystals in heterogeneous nucleation. Carboxyl groups in humic acid reduced heterogeneous nucleation rate of vivianite. Carboxyl groups in humic acid increased the growth rate of vivianite crystals. Aliphatic carboxyl groups led to larger vivianite crystal compared to aromatic ones.